无级变速谐波传动原理与传动比计算 - 辛洪兵 (Jixie chuandong)
By making relative movement between the flexible spline and rigid spline,either of them has a taper hole or taper surface,this results in the perimeter difference 2(（R-r）of flexible spline and rigid spline continuous variation, then realizes continuous variable transmission of the radial harmonic drive with inner wave generator,the radial harmonic drive with outer wave generator,the face harmonic drive,the hermitical harmonic drive and the multi-stage harmonic drive etc..Based on this measure,the radial harmonic drive device with inner wave generator is contrived.Calculation shows that the continuous variable transmission of harmonic drive can provide high variable transmission ratio,and the higher the maximum transmission ratio is required,the higher precision the flexspline and rigid spline needed.